Ocular assessment in premature infants treated for retinopathy of prematurity with intravitreal anti-VEGF injection - Oziębło-Kupczyk, Monika; Bakunowicz-Łazarczyk, Alina; Sielicka, Danuta (Klinika Oczna / Acta Ophthalmologica Polonica, 2017)
Purpose : To perform ocular assessment in premature infants treated for retinopathy of prematurity with intravitreal anti-VEGF injections. Material and methods : 15 premature infants were treated for severe retinopathy of prematurity with intravitreal anti-VEGF injections in 2011–2016. A comprehensive ocular assessment including anterior segment, fundus, visual acuity and refraction, as well as ocular ultrasound and optical coherence tomography was performed in all children. Results : A complete remission was obtained in all patients. In 4 patients, refractive errors were observed (1 – myopia, 3 – astigmatism). 3 patients had nystagmus and 6 had strabismus. In 4 children, we suspected optic nerve atrophy. Conclusions : Retinopathy of prematurity can be effectively treated with intravitreal anti-VEGF injections. Good functional and structural outcomes were achieved in all examined eyes. No ocular or systemic complications of the discussed treatment have been observed.